Lexical-semantic group "the names of clothes" is in the novel of Vasyl Shklyar "Zalyshenez. Chornyi Voron" (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the structural-semantic features of  lexical units that mark the names of clothes. The generic and concrete categories of names are distinguished. Other names are differentiated in accordance with functional using of items that mean: а) the names of head-dresses; б) the names clothes; в) the names of shoes. The pragmatic potential of the stylistically limited vocabulary is found out in concrete speech situations.
Keywords: lexical-semantic group; names of clothes; seme; stylistic features; meaning